Philanthropic Activities in Early 20th Century Vilnius: Vilnius Children’s Welfare Society’s Photo Album - Kruopienė, Milda (Lietuvos istorijos studijos, 2023)
The article examines how the 1906 photo album of the Vilnius Children’s Welfare Society (1901–1940) serves as a reflection of the child-care practices employed by philanthropic organizations in early 20th-century Vilnius. This representational source reveals the society’s aspiration to engage in philanthropic activities by providing children the skills necessary for various professions and fostering their comprehensive development of the body, soul, and mind. The purposefully arranged mise-en-scènes within the photo album also depict the image of the organization that its members sought to create.
Keywords: philanthropy; Vilnius Children’s Welfare Society; photo album